Phytophotodermatitis bullosa in an elderly patient - Jermendy, Gyorgy; Visolyi, Gergely (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Phytophotodermatitis is a phototoxic cutaneous eruption due to skin exposure to furocoumarins, which are organic chemical compounds produced by a variety of plants, and ultraviolet radiation from sunlight. Mild skin lesions can be observed relatively often among children and adolescents [1]. Severe cases (phytophotodermatitis bullosa corresponding to burn injury grade I–II) are rare, mostly occur in adulthood among gardeners and farmers. In certain geographical locations, especially in Europe, Giant Hogweed (Heracleum mantegazzianum) and Sosnowskyi Hogweed (Heracleum sosnowskyi) are particularly implicated in causing such skin lesions [2–4]. Among other inducing factors, citrus fruits (lemons, limes), fig, celeries, parsley, or carrot leaves should be noted [5–10]. Phytophotodermatitis may also be an occupational disease among grounds operatives [11].